Overexpression of ZmIPT2 gene delays leaf senescence and improves grain yield in maize - Song, Yongfeng; Li, Chunxiang; Zhu, Yong; Guo, Pei; Wang, Qi; Zhang, Lin; Wang, Zhenhua; Di, Hong (Frontiers in Plant Science, 2022)
Cytokinins (CTKs) are a major phytohormone group that are significant in the promotion of cellular division, growth, and divergence. Isopentenyl transferase (IPT) regulates a rate-limiting step in plant CTK synthesis, promotes the synthesis of isopentenyl adenonucleotides from 5-AMP and isopentenyl pyrophosphate, and then converts both these chemicals into various CTKs. Here, the full-length cDNA of ZmIPT2, which encodes 322 amino acids, was isolated and was introduced into a maize inbred line by Agrobacterium-mediated transformation. In both controlled environments and field experiments, the overexpression of ZmIPT2 gene in the transformed plants delayed leaf senescence. Compared to the receptor line, the transgenic maize lines retained higher chlorophyll levels, photosynthetic rates, and cytokinin content for an extended period of time, and produced significantly higher grain yield by a margin of 17.71–20.29% under normal field planting conditions. Subsequently, ten possible genes that interacted with ZmIPT2 were analyzed by qRT-PCR, showing that the expression pattern of GRMZM2G022904 was consistent with ZmIPT2 expression. Through comprehensive analysis, we screened for transgenic lines with stable inheritance of ZmIPT2 gene, clear functional efficiency, and significant yield improvement, in order to provide theoretical basis and material support for the breeding of new high-yield transgenic maize varieties.